Perbandingan Sistem Pendidikan Vokasi Indonesia dengan Belanda - Yuliani Fitri; Nurhizrah Gistituati; Rusdinal Rusdinal; Azwar Ananda (Departement of Mathematics Education, 2024)
The aim of this research is to determine the differences between the vocational education system in Indonesia and the Netherlands. The type of research is descriptive qualitative with a literature study method. The author uses qualitative methods by collecting data from various libraries, reading, taking notes and processing from various library sources related to the vocational education system in Indonesia and the Netherlands. From the results of the analysis it can be concluded that vocational education in Indonesia is implemented through Vocational High Schools (SMK), various polytechnics, academies, and various private and tertiary institutions. However, students who graduate from vocational school are not required to continue to vocational education at a higher level, whereas in the Netherlands it is planned earlier when students complete primary education. Students are directed to attend vocational preparatory secondary education (VMBO) and continue on to vocational higher education (MBO). In this way, this system is more effective in producing competent graduates because from the start it has been trained to focus on certain fields.